Development of a Secure Blockchain-Based System for Medical Certificate Generation and Verification (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The healthcare industry’s growing reliance on electronic medical records (EMRs) brings challenges like fraud, tampering, and unauthorized access. Blockchain technology, with its security and immutability, offers a robust solution to these issues. This project introduces a blockchain-based medical certificate generator to securely store and verify medical certificates. The system enables authorized healthcare providers to issue tamper-proof certificates that can be easily verified by patients, insurance companies, and other stakeholders. Additionally, it offers a transparent audit trail for all certificate transactions, ensuring trust and accountability. The proposed system has three core components: a smart contract, a dedicated blockchain network, and a web application. The smart contract manages the storage, issuance, and verification of certificates on the blockchain. The dedicated blockchain network guarantees the security and immutability of these records, preventing unauthorized changes. The web application offers a user-friendly interface for both healthcare providers and patients, facilitating seamless interaction with the system. This approach not only strengthens the security of medical certificates but also simplifies the verification process, reducing the risk of fraudulent documents and enhancing the integrity of digital health data.